2020
DOI: 10.1177/1941738120904944
|View full text |Cite
|
Sign up to set email alerts
|

Lesser Metatarsophalangeal Instability: Diagnosis and Conservative Management of a Common Cause of Metatarsalgia

Abstract: Context: Lesser metatarsophalangeal (MTP) instability is a common condition that can become debilitating and require surgery. Evidence Acquisition: An extensive literature review was performed through MEDLINE and Google Scholar for publications relating to the etiology, diagnosis, and treatment of lesser MTP instability using the keywords metatarsophalangeal instability, athlete, forefoot pain, and metatarsalgia from database inception to 2019. Study Design: Clinical review. Level of Evidence: Level 4. Results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 37 publications
0
4
0
Order By: Relevance
“…Conservative treatment aims to control biomechanical disorders causing metatarsal overload in order to reduce local plantar pressure and lead the patient to a subclinical condition, slowing down deformity progression [ 6 , 20 , 34 ]. Multiple conservative options have been described, such as nonsteroidal anti-inflammatory drug administration, physical therapy, plantar foot orthosis, cushioning metatarsal pads and footwear modifications [ 18 , 32 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Conservative treatment aims to control biomechanical disorders causing metatarsal overload in order to reduce local plantar pressure and lead the patient to a subclinical condition, slowing down deformity progression [ 6 , 20 , 34 ]. Multiple conservative options have been described, such as nonsteroidal anti-inflammatory drug administration, physical therapy, plantar foot orthosis, cushioning metatarsal pads and footwear modifications [ 18 , 32 , 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…3,6,14,25 Conservative treatment aims to control biomechanical disorders causing metatarsal overload in order to reduce local plantar pressure and lead the patient to a subclinical condition, slowing down deformity progression. 6,20,34 Multiple conservative options have been described, such as nonsteroidal antiin ammatory drug administration, physical therapy, plantar orthosis, cushioning metatarsal pads and footwear modi cations. 18,32,35 The metatarsophalangeal stabilizing taping technique described by Yu et al has shown good results as a provisional treatment in propulsive metatarsalgia, reducing the phalanx dorsal luxation and synovitis, although, in order to be effective, it may have to be carried out for several months.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several off-the-shelf insoles, studies on these insoles lack objective clinical data. Comparable devices such as at the Darco PegAssist are meant to offload, but there is no current data outside of metatarsophalangeal instability, 1 or studies evaluating pain using the device itself without any additional treatment provided to all groups. 2 There has been a paucity of studies to date using validated patient-reported outcome measures (PROMs) in foot offloading literature.…”
Section: Introductionmentioning
confidence: 99%
“…Although there are several off-the-shelf insoles, studies on these insoles lack objective clinical data. Comparable devices such as at the Darco PegAssist are meant to offload, but there is no current data outside of metatarsophalangeal instability, 1 or studies evaluating pain using Related Digital Media are available in the full-text version of the article on www.PRSGlobalOpen.com. Summary: Pressure offloading is often considered a crucial factor affecting healing after a foot injury.…”
Section: Introductionmentioning
confidence: 99%